Exploiting the Biginelli reaction: nitrogen-rich pyrimidine-based tercyclic α-helix mimetics. Issue 9 (3rd March 2016) - Lim, Zelong; Duggan, Peter J.; Wan, Soo San; Lessene, Guillaume; Meyer, Adam G.; Tuck, Kellie L.
Abstract: Several rationally designed pyrimidine-based scaffolds intended to mimic the spatial projection of the i, i +3, and i +7 residues of an α-helix and also possess improved aqueous solubility were prepared. A Biginelli-oxidation process was used to form the central pyrimidine ring of these scaffolds, which was subsequently manipulated to form pyrimidine-based tercyclic α-helix mimetics. A pyrimidine-based scaffold designed to mimic the α-helical BH3 domain of the pro-apoptotic Bak protein was also prepared as a putative inhibitor of the Bcl-xL /Bak protein-protein interaction. The pyrimidine-based tercyclic α-helix mimetics, and the putative Bcl-xL inhibitor, were assessed using a luminescence competition assay, however, none displayed inhibitory activity against Bcl-xL or Mcl-1. Graphical abstract: